Crescer Menire: Educação, aprendizado e agência entre as mulheres Mebengokre (Kayapó) - Pereira, Thaís de Souza (2019)
This dissertation expresses my perceptions about the formation of Mebengokre women from my experiences in the A'Ukre village in recent years. Their primary relationships and the way these relationships are dealt with in daily life and throughout life are discussed here; their methods of teaching and learning; the introduction of kuben (foreign) elements into their daily lives, examples being the village's birthday party and football championships; and the perceptions of gender and female agency Mebengokre. The Mebengokre's experiences with their relatives of the same gender and age groups, with whom they grow and begin to explore the environment with great freedom are of particular importance of learning among them. With her group of maternal relatives of close age, the menire go through all phases of life, sharing most of the everyday moments. In contrast to the view that Mebengokre women are relegated to the domestic sphere, being characterized as submissive while men monopolize the public sphere, the Mebengokre female agency is notable, which is expressed both in their traditional activities such as painting, harvesting and care in the fields, participation in festivals as well as their importance in the family structure, politically and economically.